Effect of 2.4-d exogenous application on the abscission and fruit growth in sweet orange. var. salustiana. (2012)
The effect of 2.4-D applications in full bloom on the abscission and fruit growth process was studied on sweet orange fruit in 20-year-old trees of Citrus sinensis (L.) Osbeck cv. Salustiana with a high flowering level. Abscission was determined on the whole tree and on the leafy inflorescences. Growth variables of the fruit were characterized (diameter, fresh and dry weight). 2.4-D application (20 mg L-1, 3.6 L per tree) increased the growth rate of the fruits and fruits size at maturity, however reduced the number of fruits which kept constant the yield at harvest. Differences between the diameter of the control fruits and the fruits treated with 2.4-D were observed during the early fruitlet development and until day 43 after anthesis. These differences increased with time following a linear relationship. For all the studied variables the diary increase level reaches the maximum by day 53, when the cell expansion of the vesicles starts.